Analisis Faktor-Faktor Yang Berhubungan Dengan Pengetahuan Pencegahan Karies Pada Pasien Poli Gigi UPTD Puskesmas Pattopakang Kabupaten Takalar - Febi Magfirah; Nurafni Suid (Window of Public Health Journal, 2026)
Caries is one of the oral and dental health problems that is still widely experienced by the community. Caries is a disease that damages the hard tissues of the teeth, namely enamel, dentin, and cementum. The high incidence of caries is influenced by various factors, one of which is knowledge. Good knowledge regarding caries prevention can encourage individuals to adopt oral health–maintaining behaviors, thereby reducing the risk of caries occurrence. This study aims to analyze the factors related to knowledge of caries prevention among dental clinic patients at UPTD Puskesmas Pattopakang, Takalar Regency. This study is quantitative research with a cross-sectional design. The sample consisted of 54 respondents selected using a total sampling technique. Data were collected using a questionnaire and then analyzed using the Chi-square test. The results showed that there was a significant relationship between age and knowledge of caries prevention (p = 0.003), gender and knowledge of caries prevention (p = 0.001), and education level and knowledge of caries prevention (p = 0.001). Good knowledge of caries prevention was most commonly found in the 26–35 years age group, among female respondents, and among respondents with a university education. The conclusion of this study is that there is a significant relationship between age, gender, and education level with knowledge of caries prevention among dental clinic patients at UPTD Puskesmas Pattopakang, Takalar Regency. More intensive oral health education tailored to respondents’ characteristics is needed to improve public knowledge about caries prevention.